Developing natural mentoring relationships among Latinx youth: the roles of trust in adults and stressors. Issue 2 (3rd April 2022) - Monjaras-Gaytan, Lidia Y.; Sánchez, Bernadette; Smith Carter, Jocelyn
Abstract: Mentoring is one avenue to support Latinx adolescents in their positive development. The current study examined the roles of stressors and interpersonal trust toward adults in the formation and quality (instrumental and relational) of natural mentoring relationships. Participants were 347 Latinx adolescents who were surveyed in the 9th and 10th grades. Analyses demonstrated that more trust toward adults in 9th grade was not significantly associated with the formation of a new mentoring relationship in 10th grade but was associated with higher instrumental and relational mentoring quality in 10th grade. Furthermore, reporting more life stressors in 9th grade significantly predicted the formation of new mentoring relationships but lower relational quality in 10th grade. This study fills gaps in the literature on youth and environmental characteristics that predict the development of new natural mentoring relationships over time in a Latinx sample. Implications for future research and interventions are discussed.